2021
DOI: 10.1007/s00464-021-08542-7
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes associated with the use of a new powered circular stapler for left-sided colorectal reconstructions: a propensity score matching-adjusted indirect comparison with manual circular staplers

Abstract: Background This was a retrospective, matching-adjusted indirect comparison of clinical outcomes between patients from a single-arm trial of the ECHELON CIRCULAR™ Powered Stapler (ECP) and those from a historical cohort of patients who underwent left-sided colorectal resection using conventional manual circular staplers, extracted from the Premier Healthcare Database. Methods Patients in the ECP trial cohort were propensity score matched to those in the his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 17 publications
3
35
2
Order By: Relevance
“…The current budget impact model is based on a previously completed MAIC analysis that demonstrates the superior comparative effectiveness of ECP vs manual circular staplers with respect to fewer anastomotic leaks as well as lower rates of 30-day readmissions. 26 The present model demonstrates the potential savings associated with use of ECP, which offset the higher price of the device, and provides an economic rationale for the adoption of the ECHELON CIRCULAR™ Powered Stapler in patients undergoing left-sided colorectal reconstructions.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The current budget impact model is based on a previously completed MAIC analysis that demonstrates the superior comparative effectiveness of ECP vs manual circular staplers with respect to fewer anastomotic leaks as well as lower rates of 30-day readmissions. 26 The present model demonstrates the potential savings associated with use of ECP, which offset the higher price of the device, and provides an economic rationale for the adoption of the ECHELON CIRCULAR™ Powered Stapler in patients undergoing left-sided colorectal reconstructions.…”
Section: Discussionmentioning
confidence: 78%
“…Several model limitations should be noted, however. Although real-world evidence was leveraged for the model where available, the inputs for the rates of anastomotic leak complication with ECP were from an MAIC analysis 26 which used data inputs from both a prospective clinical study (ECP group) 25 and retrospective hospital billing data analysis (SOC). It is possible that patients in a clinical trial setting may experience fewer complications due to trial protocols that require increased monitoring and patient management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pla-Marti et al in a retrospective study reported a statistically significant lower rate (1.7%) of anastomotic leak among left-sided stapled colorectal anastomosis procedures using ECP, as compared to 11.8% using manual circular staplers [ 4 ]. An indirect comparison between the ECP cohort from a single-arm trial and a matched historical cohort of patients who used manual staplers also presented a lower anastomotic leak rate (1.8% vs. 6.9%), as well as other complication rates and 30-day readmission [ 9 ]. The economic benefit of ECP is anticipated because of the avoidance of complications and readmission.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, various surgical techniques have been devised. For example, an evaluation of the intestinal blood flow using indocyanine green (ICG) fluorescent [ 6 , 7 ], sufficient mobilization of the left colon including splenic flexure for tension-free anastomosis [ 8 , 9 ], improvements in stapling devices [ 10 , 11 ] and the placement of a transanal tube for decompression of anastomosis [ 12 , 13 ]. However, anastomotic leakage in rectal surgery remains one of the most serious postoperative complications.…”
Section: Introductionmentioning
confidence: 99%